Analysis of The Income Level of Street Vendors in Besitang Market Langkat Regency - Bintang Akbar Azhari; Muhammad Yafiz; Muhammad Ikhsan Harahap (Jurnal Manajemen Bisnis, 2024)
Street trading plays a significant role in the urban economy, contributing to the livelihoods of several micro traders and opportunities for consumers to obtain goods and services at affordable prices. This research aims to conduct an in-depth analysis of street vendors' income by considering several factors that influence their economic welfare. This study involved a field survey at Besitang Market. Data was collected through direct interviews with traders, field observations, and analysis of related documents. Based on the results and discussion, the economic conditions of street vendors at Besitang Market are influenced by factors such as competition with other traders, reduced customer interest, and high operational costs. Apart from that, the type of merchandise also influences the trader's income level. Therefore, market management strategies and support from the local government are needed to increase the income and welfare of street vendors at Besitang Market, Langkat Regency.